Grain size effects on irradiated CeO2, ThO2, and UO2. (November 2018) - Cureton, William F.; Palomares, Raul I.; Walters, Jeffrey; Tracy, Cameron L.; Chen, Chien-Hung; Ewing, Rodney C.; Baldinozzi, Gianguido; Lian, Jie; Trautmann, Christina; Lang, Maik
Abstract: Microcrystalline and nanocrystalline UO2, ThO2, and CeO2 (∼2 μm and∼20 nm particle size, respectively) were irradiated with 946 MeV Au ions at room temperature and characterized by synchrotron X-ray diffraction, Raman spectroscopy, and transmission electron microscopy. All samples show a small increase in unit cell parameter as a function of ion fluence (0.17 ± 0.03% for CeO2 and 0.11 ± 0.03% for ThO2 ), except microcrystalline UO2, which displays a small contraction of the unit cell (−0.06 ± 0.02%). Raman spectroscopy measurements of microcrystalline UO2 indicate an increase in nonstoichiometry after irradiation. All bulk materials are subject to an increase in heterogeneous microstrain, most notably UO2, implying that the relatively small changes in unit cell parameter are accompanied by substantial local disorder induced by isolated defects. The magnitude of volumetric swelling for all materials is larger in the nanocrystalline form as compared with the microcrystalline form (0.38 ± 0.60% for CeO2, 0.14 ± 0.03% for ThO2, and 0.52 ± 0.13% for UO2 ). ThO2 shows the smallest difference in swelling between the microcrystalline and nanocrystalline samples (∼0.03%). All nanocrystalline materials exhibit irradiation-induced grain coarsening along with a decrease in heterogeneous microstrain with increasing ion fluence, except nanocrystalline CeO2, which shows no observable change in grain size and a slight increase in heterogeneous microstrain attributed to the accelerated formation of a secondary Ce11 O20 phase evidenced in the X-ray diffraction data, present in both nanocrystalline and microcrystalline materials. Surprisingly, nanocrystalline UO2 exhibits a significant degree of swelling indicative of a decrease in oxygen content along with an increase in disorder induced by oxygen loss at grain boundaries during irradiation, based on the analysis of X-ray diffraction and Raman spectroscopy. Graphical abstract: Image 1